A Spatio-Temporal Analysis of River Channel Migration & Erosion-Depositional Pattern of Lower Part of the Dikrong River of Assam by Using Geo-Spatial Technology - Prakasam, C; Pathak, Manisha (Indonesian Journal of Geography, 2025)
Rivers often show different morphological changes in different periods and geographical areas; a river's morphology changes due to erosion, deposition & transportation processes to attain the equilibrium state. The activity of erosion & deposition is highest in the alluvial River as a result of the river channel migration, which affects the land cover and the livelihood of the inhabitants. The Dikrang River is the northern sub-tributary of Brahmaputra, which originates in Arunachal Pradesh and flows through the Brahmaputra valley. As a result of the erosion and deposition, both the river channels have migrated, this changes the equilibrium state of the River’s aquatic environment and modifies the land use pattern in the floodplain. The objective of the present study is to identify the River channel migration pattern & the erosion-depositional scenario of the Dikrong River channel from the period of 1973-2022 to identified the responsible factors of the hazard that may helpful for the better management of the River channel. The Survey of India topographical map, LANDSAT satellite images, and geospatial tools have been applied to measure the bank line migration of the Dikrong River. The output of the study represents that the remarkable channel migration occurred in the River due to the vast sedimentation & ongoing erosion activity on both banks of the River. The lower and central parts of the river channel have gradually changed the course of the River both in the direction of the West and East of the Dikrang River channel. The study will be helpful for the planners & geomorphologists in preparing an effective management strategy to solve the problem & proper development of the watershed.Received: 2024-07-27  Revised: 2024-08-20 Accepted: 2025-07-06 Published: 2025-07-31